2013
DOI: 10.1080/00368121.2013.846899
|View full text |Cite
|
Sign up to set email alerts
|

Pop-Up Constructions Motivate and Reinforce Science Learning for Upper Elementary Students

Abstract: Pop-up boxes and folder constructions support student inquiry while integrating art, craft, spatial, and creativity skills.Step-by-step illustrated directions for constructing pop-up boxes are provided with example images of pop-up boxes focused on ecological issues. Teachers used these pop-up constructions to assist fourth-and fifth-grade students in understanding environmental problems with youth-implemented solutions. Classroom testing showed that combining art with science through pop-up constructions allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Foldables can often fall into the category of origami, or paper folding, which is a form of art. Research has long shown that integrating art into learning boosts student performance across many subjects (Olsen et al, 2013). In addition to helping students retain information, graphic organizers and foldables can help provide learning of complex and problematic topics more easily (Ayverdi et al, 2014).…”
Section: Increase Retention and Make Topics Easiermentioning
confidence: 99%
See 1 more Smart Citation
“…Foldables can often fall into the category of origami, or paper folding, which is a form of art. Research has long shown that integrating art into learning boosts student performance across many subjects (Olsen et al, 2013). In addition to helping students retain information, graphic organizers and foldables can help provide learning of complex and problematic topics more easily (Ayverdi et al, 2014).…”
Section: Increase Retention and Make Topics Easiermentioning
confidence: 99%
“…Previous studies have found that students enjoy the aspects of cutting and folding paper many ways and the kinesthetic component of physically folding paper (Lapp et al, 2015;Vivian & Wisker, 2008). Researchers agree that for foldables to have the desired effect on students' outlook on learning they should be organic, messy, and easy to make (Fisher & Frey, 2018;Olsen et al 2013). Fisher and Frey (2018) best described the benefit of foldables and graphic organizers by saying, "we can increase the likelihood that students will take pride in their work when we use graphic organizers to facilitate students' thinking about the content they are learning" (p. 766).…”
Section: Sense Of Ownership and Enjoyablementioning
confidence: 99%
“…Belajar dengan media Pop Up dapat memberikan kesempatan anak memanipulasi objek sehingga hal tersebut menstimulai perkembangan kognitif anak. Bermain menurut Piaget berkaitan dengan perkembangan kognitif ketika anak memisahkan dan menggabungkan jenis permainan dengan imajinasinya (Olsen, Zhbanova, Parpucu, Alkouri & Rule, 2013). Media pembelajaran dalam pendidikan anak usia dini dapat berbentuk satu dimensi, dua dimensi dan tiga dimensi.…”
Section: Pendahuluanunclassified
“…Thomas and Chan (2013) studied art students in Australia with a longitudinal research; They noted that art education has improved the creativity of students and achieved success. Reynolds (2012) identifies that creativity can be called through reading and writing, also Song (2012) claims that environmental science can be exploited to improve creativity; While Olsen, Zhbanova, Parpucu, Alkouri and Rule (2013) state that handicrafts are important in moving books and tools to improve creativity, Bradford (2012) and Henriksen (2005) identify that the environment and project regimes are influential in creativity; Kaczmarek (2012) and Lane (2012) point out that the intrinsic motivation is important in creativity in their work, and Ruppert (2010) indicates that developing creativity is important in the economy and business life of the country.…”
Section: Gifted Education and Creativitymentioning
confidence: 99%